Penerapan Prinsip Keadilan dan Kemanfaatan dalam Pengaturan Penghentian Penyidikan Tindak Pidana Pemilihan Kepala Daerah Karena Kedaluwarsa di Indonesia - Merlince Naomi Kedu; Simplexius Asa; Saryono Yohanes (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The regulation of the 14-day time limit for investigating regional head election crimes, as stipulated in Article 146 of Law Number 10 of 2016 concerning the election of governors, regents, and mayors, was established to accelerate law enforcement, ensure legal certainty, and maintain the relevance of election crime resolution within the strict and sequential stages of elections. However, in practice, this provision often creates legal problems when investigations must be terminated due to the expiration of the time limit, even though strong indications of election crimes exist. This situation raises a legal issue because law enforcement, although procedurally compliant, does not fully achieve substantive justice and legal utility, particularly in maintaining public trust, legal order, and democratic integrity. This study aims to analyze the theoretical basis of the 14-day investigation limit and examine the application of justice and legal utility principles in terminating election crime investigations due to time expiration. The research uses a normative legal method with statutory, conceptual, and analytical approaches. The findings indicate that the 14-day limit is grounded in the principle of lex specialis, legal certainty, speedy trial principles, electoral justice theory, and the effectiveness of integrated law enforcement. This limitation is intended to prevent prolonged legal processes, protect the legal status of reported parties, ensure smooth election stages, and maintain regional democratic stability.